Trilce or the forged instrument - Lespada, Gustavo (2022)
César Vallejo’s poetics has often been noted for the singular convergence of a radical exploration of language with a forceful social commitment. Likewise, the author is characterized by formal experimentation, and the complexity of his figures alternate with expressions of orality along with popular and historical references. But, in addition, his poetry embodies the heterogeneous conjunction produced by the impact of modernity and the persistence of the original culture; and, in this sense, it is also example of a critical and aesthetic response of a continent to the trauma of conquest. Although in Los heraldos negros (1919) we can already perceive themes and procedures of this search for his own voice, we believe that his lyrical instrument is finally forged, in all its dimension and transcendence, in Trilce (1922).